Determining indentation fracture toughness of ceramics by finite element method using virtual crack closure technique. (15th June 2018) - Sun, Liang; Ma, Dejun; Wang, Lizhi; Shi, Xinzheng; Wang, Jialiang; Chen, Wei
Highlights: A new approach to determine indentation fracture toughness by using FEM and VCCT is presented. Equi-SIF crack fronts are designed. Significance of equi-SIF crack front to the determination accuracy is revealed. The approach is potential to predict the crack pattern of certain Vickers indentation fracture test. Abstract: Based on indentation cracks produced by Vickers indentation tests on Silicon Nitride and Fused Silica, fracture toughness ( K IC ) of the two materials was determined by a Vickers indentation finite element model using virtual crack closure technique (VCCT). The elastic modulus and yield stress of the materials needed in finite element simulation were determined by using dimensionless expressions specially established for ceramic materials, which revealed the approximate numerical relationship between indentation responses and elastoplastic properties of ceramic materials. Computed K IC was obtained by calculating the stress intensity factor ( K I ) at crack tip. Considering that the calculated stress intensity factor ( K I ) varied distinctly along an ideal semi-circle crack front, the equi- K I crack front was acquired through successive simulation and adjustment. By comparison, the computed K IC values of equi- K I crack fronts were in good consistence with the reference K IC of the two materials, while those of the semi-circle crack fronts presented significant errors. The results indicated that indentation fracture toughness could be well determined by employing finite element method (FEM) and VCCT, and the obtainment of equi- K I crack front was crucial to the accuracy of computed fracture toughness.